Elucidation of the growth mechanism of MoS2 during the CVD process. (26th December 2018) - Withanage, Sajeevi S; Lopez, Mike; Sameen, Wasee; Charles, Vanessa; Khondaker, Saiful I
ABSTRACT: Chemical vapor deposition (CVD) growth of two-dimensional molybdenum disulfide (MoS2 ) using molybdenum trioxide (MoO3 ) and sulfur (S) powder often results in intermediate molybdenum oxy-sulfide (MoOS2 ) species along with MoS2 due to a lack of control over the vapor pressure required for the clean growth. Much effort has been devoted in understanding and controlling of these intermediate MoOS2 specifies. Here, we show that with a second step sulfurization at moderate temperatures, these MoOS2 crystals can be transformed to monolayer MoS2 crystals. Scanning electron microscopy, Raman and photoluminescence spectroscopy and atomic force microscopy characterization carried out before and after re-sulfurization confirm the monolayer MoS2 growth via this route. This study shows that MoOS2 formed at the intermediate state can be successfully recycled to MoS2 .